A transparent TiO2–C@TiO2–graphene free-standing film with enhanced visible light photocatalysis. Issue 49 (3rd May 2016) - Hu, Luyang; Zhang, Yumin; Zhang, Shanmei; Li, Benxia
Abstract : A transparent TiO2 –C@TiO2 –graphene free-standing film with graphene wrapped flower-like TiO2 particles on C–TiO2 fibers is synthesized for visible light photocatalysis. Abstract : A transparent TiO2 –C@TiO2 –graphene free-standing film has been synthesized by electrostatical self-assembling GO nanosheets on a cellulose–TiO2 @TiO2 film prepared by a one-step hydrothermal method followed by thermal annealing at 500 °C. Scanning and transmission electron microscope observations have shown graphene wrapped flower-like micro/nanostructure TiO2 particles uniformly distribute on TiO2 –C fibers that are interconnected with each other to form a 3D reticulate microstructure. X-ray photoelectron spectra have demonstrated that interaction between the TiO2 and graphene facilitates the generation of O–Ti 3+ species and Ti–O–C bonds. As a result, the TiO2 –C@TiO2 –graphene film exhibits a significant enhancement of light absorption within the visible region as compared to the TiO2 –C@TiO2 film. Meanwhile, the introduction of a graphene layer slows the recombination of photogenerated electron–hole pairs, increasing the charge transfer rate of electrons. Thus, in the photocatalytic degradation reaction of methylene blue, the photodegradation rate constant for the TiO2 –C@TiO2 –graphene film is 2.2 times higher than that of the TiO2 –C@TiO2 film obtained from thermal treatment of the cellulose–TiO2 @TiO2 film. The enhanced photocatalytic property is well consistent with the photoelectrical responses, electrochemical impedance spectroscopy analyses and photoluminescence spectra results. This work may provide a rational and convenient strategy to construct transparent free-standing films with visible light photocatalysis toward environmental purification.